Urban furniture design and ergonomic assessment in neighborhood parks: the case of Fabrika District, Diyarbakır, Türkiye - Akin, Kubra Aktas; Unal, Muge (Bekir Cihad Bal, 2025)
Neighborhood parks are essential public spaces encouraging socialization, physical activity, and relaxation. Their effective use is closely tied to the ergonomic design of urban furniture. This study evaluates the ergonomic suitability of urban furniture in four parks in the Fabrika Neighborhood, Yenişehir District, Diyarbakır by using a qualitative assessment method. The research was conducted in four stages: (1) A literature review identified 13 sub-criteria under six main categories: material, ergonomics, inclusive design, color, safety, and vandalism. (2) Fieldwork conducted between November and December 2024 assessed 18 types of urban furniture using a 0–5 rating scale. (3) Parks were classified based on their ergonomic performance. (4) Recommendations were developed to enhance usability. The findings revealed that NP1 (42.1%), NP2 (42.0%), and NP3 (41.6%) were "moderately suitable" while NP4 (26.4%) was "less suitable." Deficiencies were particularly noted in ergonomics, safety, and inclusive design. Unlike previous studies, this research integrates ergonomic criteria for a comprehensive evaluation. Future studies should prioritize sustainable, technology-based solutions to enhance urban furniture design. © 2025, Bekir Cihad Bal. All rights reserved.
Mahalle parklarında kent mobilyası tasarımı ve ergonomik değerlendirme: Fabrika Mahallesi örneği, Diyarbakır-Türkiye
Keywords: Ergonomics; Neighbourhood parks; Urban furniture; Urban life quality